Implication of Cigarette Tax as Remote Working Receiving Regional Income Community Health in Banten Province in 2017 - 2018 - Suhaili, Ahmad; Sari, Gema Ika (APTISI Transactions on Management (ATM), 2021)
Law No. 28 of 2009 article 31 paragraph (1) of cigarette tax revenue-sharing funds, is allocated at least 50% (fifty percent) to fund health services and law enforcement by the authorities. Banten Provincial Health Office. Said that the level of public health from the number of diseases tends to increase. The research method used in this study is a descriptive method, with quantitative data collection techniques namely data on cigarette tax revenues in Banten province, and expenditure data on expenditure in the Banten Provincial Health Office, the qualitative data uses interviews, observations, and documentation. The results of this study are for the effectiveness level of cigarette tax collection managed by Bapenda in 2017-2018 with an average percentage of 83% with the category quite effective, for the level of contribution of cigarette tax fund allocation to the public health of Banten province in 2017-2018 with an average 71% percentage managed by the Banten Provincial Health Office and have not been maximized because it has not used 100% of the funds for public health efforts in the province of Banten. There are several attempts made (1) making KTR, (2) conducting socialization, (3) conducting counseling.